Inhibition of in vitro transcription by 2-arylidene derivatives of thiazolo[3,2-α]benzimidazol-3(2H)-one - Palchykovska, L.G.; Alexeeva, I.V.; Negrutska, V.V.; Kostyuk, Yu.K.; Indychenko, T.M.; Kostenko, O.M.; Kryvorotenko, D.V.; Shved, A.D.; Dubey, I.Ya. (Вiopolymers and Cell, 2010)
Aim. To evaluate a series of 2-substituted thiazolo[3,2-α]benzimidazolones as potential transcription inhibitors. Methods. Compounds were tested in a model transcription system based on T7 RNA polymerase. Results. The testing revealed a number of compounds able to inhibit transcription at micromolar concentrations. The most active inhibitor was dihydroxy derivative BT29 with IC50 = 1.6 μM. Conclusions. Structure-functional dependence of the activity of tested compounds as transcription inhibitors was found. The key structural feature required for their high activity is a presence of hydroxy or dialkylamino group at p- or m-position of arylidene fragment. Мета. Дослідити серію 2-заміщених тіазоло[3,2-α]бензімідазолонів як потенційних інгібіторів транскрипції. Методи. Речовини тестували в модельній системі транскрипції на основі РНК-полімерази Т7. Результати. Тестування виявило низку сполук, здатних інгібувати транскрипцію в мікромолярних концентраціях. Найактивнішим з-поміж них є дигідроксипохідне ВТ29 з IC50 = 1,6 μM. Висновки. Встановлено залежність активності вивчених речовин як інгібіторів транскрипції від їхнього структурно-функціонального стану. Ключовим фактором, що визначає їхню високу активність, є присутність гідрокси- чи діалкіламіногрупи в п- або м-положенні ариліденового фрагмента. Цель. Исследовать серию 2-замещенных тиазоло[3,2-α]бензимидазолонов как потенциальных ингибиторов транскрипции. Методы. Вещества тестировали в модельной системе транскрипции на основе РНК-полимеразы Т7. Результаты. Тестирование выявило ряд соединений, способных ингибировать транскрипцию в микромолярных концентрациях. Наиболее активным среди них является дигидрокси-производное ВТ29 с IC50 = 1,6 μM. Выводы. Установлена зависимость активности изученных веществ как ингибиторов транскрипции от их структурно-функционального состояния. Ключевым фактором, определяющим их высокую активность, является присутствие гидрокси- или диалкиламиногруппы в п- или м-положении арилиденового фрагмента.